Infrastructure development, human development index, and CO2 emissions in China: A quantile regression approach - Liu, Yaofei; Poulová, Petra; Pražák, Pavel; Ullah, Farman; Nathaniel, Solomon Prince (Frontiers in Environmental Science, 2023)
This study investigates the relationships between infrastructure development, human development index (HDI), and CO2 emissions in China. Infrastructure has played an essential role in achieving social and economic developmental goals in China, but environmental pollution has significantly increased in the country in the last two decades. Our analysis uses time series data from 1990 to 2021 and quantile regressions, and we find that infrastructure has positive and statistically significant relationships with HDI, CO2 emissions, and GDP in all quantiles. Recent infrastructure upgrades improve living standards and increase HDI but damage the environment, and infrastructure is the main source of CO2 emissions in the country. Therefore, the government should invest in sustainable infrastructure to mitigate CO2 emissions. The government may consider infrastructure options such as low carbon transportation, including railway infrastructure, urban metros, and light rail.